The effect of breastfeeding, breast milk odour and mother's heartbeat sound on pain level in newborns: A randomized trial - KARAKOÇ, AYŞE (My University, 2022)
Aim This study aimed to compare the effects of breastfeeding, breast milk odour and mother\"s heartbeat sounds on perceived pain during heel lance procedures in term newborns. Design This was a randomized three-group experimental study. Methods The sample of the study consisted of 90 newborns. The data were collected using pulse oximeter, fetal hand doppler, voice recorder, loudspeaker, a data collection form and the ALPS-Neo Pain and Stress Assessment Scale for Newborn Infants. Results During the procedure, newborns in the breast milk odour group had high levels of pain and stress, those in the mother\"s heartbeat sounds group had mild pain and stress, and those in the breastfeeding group had no pain and stress. Additionally, a statistically significant difference was found between their crying times. This difference was the highest for newborns in the breast milk odour group, followed by the mother\"s heartbeat sounds and breastfeeding groups, respectively. Conclusion Breastfeeding and mother\"s heartbeat sounds, which are non-pharmacological pain relief methods, are effective in neonatal pain management. However, breast milk odour is not effective for pain control in newborns. Further studies should examine the efficacy combinations of these methods.
Keywords: Tıp; Sağlık Bilimleri; Hemşirelik; Medicine; Health Sciences; Nursing; HEMŞİRELİK; Klinik Tıp; Klinik Tıp (MED); NURSING; CLINICAL MEDICINE; Clinical Medicine (MED); Yoğun Bakım Hemşireliği; Tıbbi ve Cerrahi Hemşirelik; Farmakoloji (hemşirelik); Annelik ve Ebelik; Onkoloji (hemşirelik); Hemşirelik (çeşitli); İleri ve Uzman Hemşirelik; Asistan Hemşirelik; LPN ve LVN; Genel Hemşirelik; Acil Tıp Hemşireliği; Critical Care Nursing; Medical and Surgical Nursing; Pharmacology (nursing); Maternity and Midwifery; Oncology (nursing); Nursing (miscellaneous); Advanced and Specialized Nursing; Nurse Assisting; LPN and LVN; General Nursing; Emergency Nursing; breast milk odour; breastfeeding; mother's heartbeat; newborn; pain; PRETERM INFANTS; GUIDELINES; SUCKING; CARE